Venom [videorecording (Blu-Ray + DVD)] - Pinkner, Jeff; Rosenberg, Scott, 1963-; Marcel, Kelly, 1974-; Hardy, Tom, 1977-; Williams, Michelle, 1980-; Ahmed, Riz, 1982-; Haze, Scott; Scott, Reid, 1977-; Slate, Jenny, 1982-; Walters, Melora, 1960-; Libatique, Matthew, 1969-; Göransson, Ludwig, 1984-; et al. (Sony Pictures Home Entertainment, 2018)
Investigative journalist Eddie Brock attempts a comeback following a scandal, but accidentally becomes the host of an alien symbiote that gives him a violent super alter-ego. Soon, he must rely on his newfound powers to protect the world from a shadowy organization looking for a symbiote of their own.